Human Aspects of IT for the Aged Population. Design for Everyday Life First International Conference, ITAP 2015, Held as Part of HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015. Proceedings, Part II - Zhou, Jia; Salvendy, Gavriel (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2015)
The two LNCS volume set 9193-9194 constitutes the refereed proceedings of the First International Conference on Human Aspects of IT for the Aged Population, ITAP 2015, held as part of the 17th International Conference on Human-Computer Interaction, HCII 2015, held in Los Angeles, CA, USA, in August 2015, jointly with 15 other thematically conferences. The total of 1462 papers and 246 posters presented at the HCII 2015 conferences were carefully reviewed and selected from 4843 submissions. These papers of the two volume set address as follows: LNCS 9193, Design for Aging (Part I), addressing the following major topics: HCI design and evaluation methods for the elderly; ICT use and acceptance; aging, the web and social media; and the elderly and mobile devices and LNCS 9194, Design for Everyday Life (Part II), addressing the following major topics: health care technologies and services for the elderly; home and work support; smart environment and AAL; and communication, games, and entertainment.